2012
DOI: 10.1159/000339113
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of the Endocannabinoid Anandamide in Experimental Periodontitis and Stress in the Rat

Abstract: Objective: Periodontitis is an infectious disease leading to inflammation and destruction of tissue surrounding and supporting the tooth. The progress of the inflammatory response depends on the host’s immune system and risk factors such as stress. The aim of the present study was to investigate the role of the endocannabinoid anandamide (AEA) in experimental periodontitis with restraint stress, since the endocannabinoid system is known to modulate the hypothalamo-pituitary-adrenal axis as well as immune funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
40
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 85 publications
(50 reference statements)
13
40
0
7
Order By: Relevance
“…Further studies are needed to address whether such approaches are also protective in glomerular injury associated with hHcys. Our finding that exogenous AEA produces anti-inflammatory effects is consistent with several reports documenting beneficial effects of exogenous AEA in inflammatory disease models, such as liver damage (Hegde et al, 2008), LPS-induced pulmonary inflammation AEA and Metabolites and NLRP3 Inflammasomes in Podocytes (Berdyshev et al, 1998), periodontitis (Rettori et al, 2012), hypoxia-ischemia injury (Lara-Celador et al, 2012), delayedtype hypersensitivity (Jackson et al, 2014), and viral demyelinating disease (Hernangomez et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Further studies are needed to address whether such approaches are also protective in glomerular injury associated with hHcys. Our finding that exogenous AEA produces anti-inflammatory effects is consistent with several reports documenting beneficial effects of exogenous AEA in inflammatory disease models, such as liver damage (Hegde et al, 2008), LPS-induced pulmonary inflammation AEA and Metabolites and NLRP3 Inflammasomes in Podocytes (Berdyshev et al, 1998), periodontitis (Rettori et al, 2012), hypoxia-ischemia injury (Lara-Celador et al, 2012), delayedtype hypersensitivity (Jackson et al, 2014), and viral demyelinating disease (Hernangomez et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…In vitro studies show that AEA reduces the production of pro-inflammatory mediators induced by P. gingivalis lipopolysaccharide (LPS) in human gingival fibroblasts [14] and promotes the proliferation of these cells [13]. Animal studies have shown that AEA and its synthetic analog methanandamide diminish the inflammatory response in experimentally induced periodontitis [16], [17]. However, the exact role of endocannabinoid system in pathogenesis of periodontal disease remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Carignan and his group (2013) reported that aliphatic n-alkanols target nuclear factor of activated T cells (NFAT) and nuclear factor kappa-b (NF-jb) situated downstream to the cell membrane. Compounds with active amide linkage such as anandamide, inhibit TNF-a and IL-1b expression in experimental inflammatory periodontitis and stress models (Rettori et al 2012). In addition, there are numerous compounds possessing active nitro groups with diverse medicinal and therapeutic properties (Kapoor et al 2003).…”
Section: Discussionmentioning
confidence: 99%